THE CHINESE CONCEPT OF TALENTNESS IN THE IDEA OF NATIONAL PARALYMPIC MOVEMENT - Kalashnyk, Nadiia; Marakushin, Andrei; Zhanglian, Han; Yanlin, Wu; Shevchenko, Nadiia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The idea of Paralympic movement is rather new for the Chinese society, though this country started its taking part in Paralympic games` history in 1984. Traditionally the Chinese society was wary of people with physical disabilities seeing external flaws as a sign of personal inferiority and punishment of gods. The pure Chinese concept of talentness having as the basic tenet "there are no talented, there are those who are not very hardworking", also for a long time limited people with special needs in accessing sport events of a high (and even local) level. The idea of the article is to show the efforts of modern Chinese society in balance search between trends of Paralympic movement and Chinese traditional socio-psychological attitudes as to people with special needs. Such methods as interviewing, questioning, statistical data and official documents` analysis, analytic compilation were used. The following theoretical results were gained: as the Paralympic movement is not very strong in China due to its novelty, for today Paralympic athletes make up a small, almost closed group of Chinese athletes, where the criterion of talentness in a particular sport is leveled by the physical abilities and hardworking of each athlete in particular.